A clinico-pathological study of HIV-associated cystic lymphoid hyperplasia - Dulabh, Shailen (My University, 2011)
Introduction: Cystic lymphoid hyperplasia (CLH) is a common yet under recognised entity affecting the parotid gland in HIV infected patients. This is the largest global clinicopathological study of CLH to date consisting of 167 cases (85M, 82F). Aim: To define the clinical parameters, histology and immunopathological features of CLH with a view to elucidating the aetio-pathogenesis. Material and Methods: This retrospective study on archival cases of CLH included patient’s age, race, gender, nature of CLH, HIV status, CD4 counts and viral loads where available. Of the 167 confirmed cases of CLH, 109 cases were histologically reviewed and 25 cases were immunohistochemically analysed with CD3, CD20, CD4, CD8 and p24 using standard procedures. Ethics clearance (M080927 and M080850) was obtained. Results: CLH mainly affects the parotid gland with a male predominance. Submandibular gland (p = 0.27) and bilateral parotid involvement favours females (2:1). CLH affects females at a younger mean age in both the parotid and submandibular glands (36.5, 31 years) respectively compared to males (40.9, 42.4 years) (p = 0.0032). Intra-lymph nodal origin is favoured with 76.1% of cases occurring within entrapped salivary gland remnants. P24 staining reveals ~90% specificity in HIV associated CLH. Immunostaining showed a CD8:CD4 of ~1:1 except in selected cases where CD4 was decreased in the interfollicular areas. Conclusion: CLH is the preferred term to describe bilateral parotid enlargement in HIV infected patients. This study strongly supports origin of CLH following ductal ectasia of entrapped salivary gland inclusions within atypical lymphoid hyperplasia arising within lymph nodes in the context of an HIV setting. CLH should be classified as an orofacial lesion strongly associated with HIV and AIDS.
Keywords: HIV Infections; Parotid Gland; Hyperplasia